1988
DOI: 10.1002/chin.198851208
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Chorismate Mutase Inhibitors: Synthesis and Evaluation of Some Potential Transition‐State Analogues.

Abstract: ChemInform Abstract Chorismate mutases catalyze the conversion of chorismic acid (I) to prephenic acid (II). In order to evaluate potential inhibitors of these enzymes, several bicyclic molecules such as (III) -(VIII) are synthesized which mimic the presumed transition state of the rearrangement. The endo-diacid (III) is the most potent inhibitor for a chorismate mutase, while the compounds (VII) and (VIII) have only poor inhibiting activity. Structure-activity relationships are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…A milestone in the elucidation of the enzyme reaction mechanism was reached when the crystal structure of CM was solved by Lipscomb and coworkers in 1993, and refined to 2.2 Å resolution . The active site structure in complex with Bartlett's TS analog (TSA) and reaction product ( 2 ) strongly suggested that the enzymatic mechanism proceeds as a pericyclic process, similar to the uncatalyzed reaction. The structure provided the basis for the first quantum and molecular mechanics (QM/MM) study on CM, which suggested that substrate conversion may involve a combination of substrate strain and TS stabilization .…”
mentioning
confidence: 99%
“…A milestone in the elucidation of the enzyme reaction mechanism was reached when the crystal structure of CM was solved by Lipscomb and coworkers in 1993, and refined to 2.2 Å resolution . The active site structure in complex with Bartlett's TS analog (TSA) and reaction product ( 2 ) strongly suggested that the enzymatic mechanism proceeds as a pericyclic process, similar to the uncatalyzed reaction. The structure provided the basis for the first quantum and molecular mechanics (QM/MM) study on CM, which suggested that substrate conversion may involve a combination of substrate strain and TS stabilization .…”
mentioning
confidence: 99%
“…The literature reports inhibition of this and similar compounds as I 50 / K m 1 , with a value of 0.008 for the TSA [34, 35]. Similar calculations were performed for compounds 6 and 10 versus EcCM, and values of 0.05 and 0.053 were determined, better than all of the reported compounds save the TSA.…”
Section: Discussionmentioning
confidence: 52%
“…The shikimate pathway is also recognized as an attractive target for antimicrobial drug design, since mammals do not synthesize aromatic amino acids. Rational design of inhibitors has been conducted for the chorismate mutases [3138], including the TSA (transition state analogue), an oxabicyclic acid generated by Bartlett [34, 35]. EcCM is refractory to screening, because it lacks a good spectrophotometric handle and is difficult to make in sufficient quantities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have synthesized inhibitors of selected aromatic pathway enzymes in the hope they would have herbicidal activity. Enzymes for which no herbicidal activity of synthetic inhibitors was reported include shikimate dehydrogenase (Baille et al 1972;Bugg et al 1988a), dehydroquinase (Bugg et al 1988b), and chorismate mutase (Bartlett et al 1988;Clarke et al 1990). Ambiguous results were reported for 3-dehydroquinate synthase.…”
Section: Targeting the Aromatic Pathway For Herbicide Designmentioning
confidence: 99%